Commodification Practices in the Begawe Sasak’s Lombok Tradition - Abdul Rahim; Halimatuzzahro (Institut Agama Islam Negeri Madura, 2021)
The begawe tradition, which has become the popular culture of Sasaknese, has begun shifted by the consumption of mass cultures, such as catering services, the use of tools or begawe needs, starting to be replaced by industrial products for rent or sale. The forms of commodification in the begawe tradition, especially in begibung (eating together) and betulung (helping each other), two things that become the ‘aura’ of begawe. This difference can be seen from the shifting values, from the principle of kinship to individualism; of various equipment that is transformed and then commercialized. The new ethnography in this case study becomes the basis for examining the commodification practice in the begawe tradition, which switches to catering services and traditional equipment and replaces by modern equipment. The author, who is part of the Sasak community, also takes a participatory approach in begawe events held by the community. This shows that the alienation of popular culture in society cannot be contained by massive mass culture, so that people, which were initially established with high social values, began to form individualist societies that competed to show their social status. The consumption of signs/symbols has formed a society trapped in a pseudo-need that is unwittingly oppressive. Awareness to be critical and filter the mass culture needs a sphere for negotiation to return the spirit of the social community based on kinship interaction.